Introductory statistics - Ross, Sheldon M. (Burlington, MA : Academic Press/Elsevier, 2010)
In this revised text Sheldon Ross has produced a work in introductory statistics. Ross provides an explanation of intuition and the ideas behind the statistical methods. To quote from the preface, 'It is only when a student develops a feel or intuition for statistics that she or he is really on the path toward making sense of data'. Ross achieves this goal through a coherent mix of mathematical analysis, intuitive discussions and examples. This title presents historical perspective profiling prominent statisticians and historical events to motivate learning by providing interest and context. Comprehensive ancillaries include most commonly used statistical software packages (SAS, SPSS, Minitab), ISM, SSM, and graphing calculator manual all insures the most complete instructor support of any book. Use of exercises and examples helps guide the student towards independent learning using real issues and real data, e.g. stock price models, health issues, gender issues, sports, scientific fraud. Summary/Key Terms - chapters end with detailed reviews of important concepts and formulas, key terms and definitions which are useful to students as study tools. Data sets from text and exercise material will be available to download from the text website, saves students time.
Includes bibliographical references and index.
Julkaistu myös verkkokirjana.
Keywords: Mathematical statistics; matemaattinen tilastotiede; tilastot; tilastotiede